Amounts Mobilised from the Private Sector by Official Development Finance Interventions Guarantees, syndicated loans and shares in collective investment vehicles - Benn, Julia (OECD Publishing, 2016)
According to the 2015 DAC Survey on mobilisation, USD 36.4 billion was mobilised from the private sector in 2012-14 through official development finance interventions in the form of guarantees, syndicated loans and shares in collective investment vehicles (development-related investment funds). Overall flows followed an upward trend over the period covered by the survey, with guarantees mobilising the largest share (59%). Multilateral development banks took the lead in mobilising finance mostly through guarantees, followed by the national development finance institutions. Middle-income countries received the largest share of the amount mobilised, mainly targeting the energy, industry and banking sectors. Of the total amount mobilised, 19% was climate-related, most of it focusing on climate change mitigation. This working paper provides more details about the Survey results
Keywords: Development